Análisis de las actividades de niños de Educación Inicial en pueblos originarios de Oaxaca, México - Jiménez Ramírez, Julián (2015)
This study provides partial results of a 200-hour intensive training experience (called a diplomado) lasting one school year (2011-2012) for 35 indigenous teachers of Initial education who attend children 0 to 3 years old in marginalized communities of Oaxaca, mexico. Children’s spontaneous activities and those planned by teachers, presented through photographs and accompanying teacher’ narratives, are part of the written and photographic evidence submitted by the participants in their final diplomado portfolio of tasks. the purposes of the diplomado were to enrich teachers’communal knowledge and equip them with research skills to investigate and honor the communal practices, forms of governance, and the perspectives of the rural indigenous communities where they teach, in order to generate an authentic, alternative, community-based approach to initial education for babies and toddlers.